Integrated production of aromatic amines, aromatic hydrocarbon and N-heterocyclic bio-char from catalytic pyrolysis of biomass impregnated with ammonia sources over Zn/HZSM-5 catalyst. Issue 1 (February 2020) - Zheng, Yunwu; Wang, Zhen; Liu, Can; Tao, Lei; Huang, Yuanbo; Zheng, Zhifeng
Abstract: By introducing exogenous nitrogen during biomass pyrolysis under nitrogen-rich conditions, high-value nitrogen-containing products, i.e., nitrogen-rich char and oil may be produced. Based on the cogeneration of high-value nitrogen products from biomass, biomass nitrogen-enriched pyrolysis was performed in a fixed bed with different sources and contents of ammonia. The yields, composition and characteristics of the products were investigated. Moreover, the formation mechanism of N-containing species was explored in depth for the pyrolysis and catalytic pyrolysis with HZSM-5 and Zn/HZSM-5 catalysts via elemental analysis, XPS, FTIR and BET. The results showed that ammonia impregnation could promote a Maillard reaction, reduce the content of small aldehydes and ketones, and produce a nitrogen-enriched bio-oil. The contents of N-containing species and phenolic substances in the pyrolysis oil of biomass impregnated with 10% urea reached 15.66% and 56.69%, respectively. Moreover, the nitrogen on the coke surface after pretreatment was mainly composed of CN, CN and NCOO functional groups. The bio-char generated abundant pyridinic-N, pyrrolic-N, quaternary-N, and pyridone-N oxides. The presence of urea introduced many alkaline N-containing functional groups on the surface of the bio-char and promoted the transformation of nitrogen from amides and imides to heterocyclic nitrogen with higher thermal stability. Furthermore, Zn was an excellent catalyst for the Maillard reaction, and the Zn/HZSM-5 catalyst had a higher selectivity for aromatic hydrocarbons (96.98% for biomass and 86.48% for urea/biomass) and N-containing heterocyclic compounds, such as indoles (6.16% for biomass and 13.51% for urea/biomass). Additionally, the coke content decreased, and the catalyst deactivation decreased. Graphical abstract: Image 1 Highlights: N-containing chemicals and bio-char are co-generated with ammonia source impregnated. A large amount of N contained species was formed with urea introduced in. Indoles and aromatic hydrocarbon in bio-oil reached 13.51% and 86.48%with Zn/HZSM-5. Bio-char was rich of pyridininc-N, pyrrolic-N, quaternary-N, pyridone-N-oxide. The reaction mechanism for the formation of individual products was proposed.